Examining Business Performance of Indonesian MSMEs: Dynamic Capabilities that Matter - Ongkowijoyo, Gracia; Phandy, Lindsey Brittany; Gandakusuma, Nielsen (Management Analysis Journal, 2025)
The study aims to examine the influence of various dimensions of DC—sensing, learning, and integrating/coordination capabilities—on the business performance of Micro, small, and medium-sized enterprises (MSMEs), as well as the potential moderating effect of firm scale. MSMEs are integral to Indonesia's economic framework. However, their resilience is challenged by economic crises and the COVID-19 pandemic, which emphasized the importance of dynamic capabilities (DC) in adapting to volatile environments. Using a quantitative approach, data were collected via questionnaires from 51 Indonesian MSMEs. Findings indicate that learning and integrating/coordination capabilities significantly enhance business performance, while sensing capability does not. Firm scale shows no moderating effect, suggesting uniform strategies across micro, small, and medium enterprises. This study enhances the existing DC theory by elucidating the specific contributions of its dimensions within resource-limited environments and offers practical recommendations for MSME managers to focus on skill enhancement and operational effectiveness to achieve sustained growth.